CURSING BEHAVIOR BY POINTING OUT THE MIDDLE FINGER IN CHILDREN AGED 5-6 YEARS AT THE RA INSTITUTION IN GENTENG SUB-DISTRICT, BANYUWANGI REGENCY - Andriani, Viena Wanidha; Syamsudin, Moh. Anas (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Morality related to religious and cultural values are crucial things in every level of education, including early childhood education. Language, as an element that represents these values, is important in the daily communication process both at school and at home. The use of non-verbal language, namely the gesture of raising the middle finger, is a normalized taboo symbol that is interesting to study in order to be a reference in preventing or neutralizing this behavior. This research is based on two problems, how children aged 5-6 years understand the middle finger symbol and how they recognize it. This research is qualitative research with a case study approach involving 100 students of class B from 7 RA (Raudhatul Athfal) in Genteng